The Long-Term Clinical Outcome of Posttraumatic Stress Disorder With Impaired Coronary Distensibility. Issue 3 (April 2018) - Ahmadi, Naser; Hajsadeghi, Fereshteh; Nabavi, Volker; Olango, Garth; Molla, Mohammed; Budoff, Matthew; Vaidya, Nutan; Quintana, Javier; Pynoos, Robert; Hauser, Peter; Yehuda, Rachel
ABSTRACT: Objective: Coronary Distensibility Index (CDI) impairments reflect endothelial-dependent process associated with vulnerable-plaque composition. This study investigated the relation of impaired CDI with posttraumatic stress disorder (PTSD) and their predictive value for major adverse cardiovascular events (MACE). Methods: This study involved 246 patients (age = 63 [10] years, 12% women) with ( n = 50) and without ( n = 196) PTSD, who underwent computed tomography angiography to determine coronary artery disease and CDI. Extent of coronary artery disease was defined as normal, nonobstructive (<50% luminal stenosis), and obstructive (>50%). Incidence of MACE, defined as myocardial infarction or cardiovascular death, was documented during a mean follow-up of 50 months. Survival regression was employed to assess the longitudinal association of impaired CDI and PTSD with MACE. Results: A significant inverse correlation between CDI and Clinical Global Impression Severity scale of PTSD symptoms was noted ( r 2 = .81, p = .001). CDI was significantly lower in patients with PTSD (3.3 [0.2]) compared with those without PTSD (4.5 [0.3]), a finding that was more robust in women ( p < .05). Covariate-adjusted analyses revealed that the relative risk of MACE was higher in patients with PTSD (hazard ratio [HR] = 1.56, 95% CI = 1.34–3.14) and those with impaired CDI (HR = 1.95, 95% CI = 1.27–3.01, per standard deviation lower CDI value). There was also a significant interaction between PTSD and impaired CDI (HR = 3.24, 95% CI = 2.02–5.53). Conclusions: Impaired CDI is strongly associated with the severity of PTSD symptoms. Both impaired CDI and PTSD were independently associated with an increased risk of MACE during follow-up, and evidence indicated an interaction between these two factors. These findings highlight the important role of CDI in identifying individuals with PTSD at risk for MACE.